Collision Event during 177-135 Ma on the Eastern Margin of the Qinghai-Tibet Plateau: Evidence from 40Ar/ 39Ar Dating for Basalts on the Western Margin of the Yangtze Platform - Zengqian, HOU; Wen, CHEN; Jiren, LU (Acta geologica Sinica (Beijing), 2002)
Geochronology of continental flood basalts sampled from the Emei large igneous province (LIP) on the western margin of the Yangtze platform was investigated by the laser microprobe 40Ar/39Ar dating technique. These basalts yield a fairly wide range of 40Ar/39Ar ages, varying from 259 to 135 Ma. One basalt sample, at least altered, recorded the oldest 40Ar/39Ar age of about 259 Ma, corresponding to a peak eruption age of the Emei LIP continental flood basalts. Most of the samples yield much younger ages from 135 to 177 Ma, which are consistent with the K-Ar ages for the same samples (122.8-172.1 Ma). The dating data suggest that these Permian basalts had been widely affected by the regional tectonothermal event at 177-135 Ma. The event was probably caused by the convergence and collision among the Laurasia, Yangtze and Qiangtang-Qamdo continental blocks on the eastern margin of the Qinghai-Tibet plateau after the late Triassic. The age of the event reflects the timing of the peak collisional orogeny.